Analisis kualitas air sungai dan ikan lele sebagai bioindikator industri rambut di Purbalingga (Berita Kedokteran Masyarakat (BKM), 2016)
Purpose:  The purpose of this study was to analyze the quality of river water around the industry in terms of BOD, COD, TSS, Cr (VI) parameters and Cr (VI) accumulation on catfish.Method: This was an observational study, with a cross-sectional design. The study population was river water and catfish which is around the industry. The sample is determined based on the location point of the retrieval divided into 5 stations. Findings: The association of BOD, COD and TSS levels showed a positive linear relationship. Cr (VI) concentration affects the accumulation of Cr (VI) on gill catfish.Practical implications: This study demonstrates the need for river water surveillance, to be free from contamination of organic substances and heavy metals. The quality of river water is related to the quality of catfish.Originality: The concentration of BOD, COD, and Cr (VI) exceeds the standard grade river quality. There are different levels of BOD and COD. The association of BOD, COD and TSS levels showed a positive linear relationship. Cr (VI) concentration affects the accumulation of Cr (VI) on gill catfish.